MicroRNAs modulate SARS-CoV-2 infection of primary human hepatocytes by regulating the entry factors ACE2 and TMPRSS2 - Khanal, Rajendra; Heinen, Natalie; Bogomolova, Alexandra; Meister, Toni L.; Herrmann, Simon T.; Westhoven, Saskia; Nocke, Maximilian K.; Todt, Daniel; Jockenhövel, Freya; Klein, Isabel M.; Hartmann, Laura; Vondran, Florian W. R.; et al. (Liver international, 2024)
Background and Aims Severe acute respiratory syndrome coronavirus (SARS-CoV-2) preferentially infects the respiratory tract; however, several studies have implicated a multi-organ involvement. Hepatic dysfunctions caused by SARS-CoV-2 infection have been increasingly recognized and described to correlate with disease severity. To elucidate molecular factors that could contribute towards hepatic infection, we concentrated on microRNAs (miRNAs), a class of small non-coding RNAs that modulate various cellular processes and which are reported to be differentially regulated during liver injury. We aimed to study the infection of primary human hepatocytes (PHH) with SARS-CoV-2 and to evaluate the potential of miRNAs for modulating viral infection. Methods We analysed liver autopsies from a coronavirus disease 19 (COVID-19)-positive cohort for the presence of viral RNA using Nanopore sequencing. PHH were used for the infection with SARS-CoV-2. The candidate miRNAs targeting angiotensin converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) were identified using in silico approaches. To discover the potential regulatory mechanism, transfection experiments, qRT-PCRs, western blots and luciferase reporter assays were performed. Results We could detect SARS-CoV-2 RNA in COVID-19-positive liver autopsies. We show that PHH express ACE2 and TMPRSS2 and can be readily infected with SARS-CoV-2, resulting in robust replication. Transfection of selected miRNA mimics reduced SARS-CoV-2 receptor expression and SARS-CoV-2 burden in PHH. In silico and biochemical analyses supported a potential direct binding of miR-141-3p to the SARS-CoV-2 genome. Conclusion We confirm that PHH are susceptible to SARS-CoV-2 infection and demonstrate selected miRNAs targeting SARS-CoV-2 entry factors and/or the viral genome reduce viral loads. These data provide novel insights into hepatic susceptibility to SARS-CoV-2 and associated dysfunctions in COVID-19.